2011
DOI: 10.1055/s-0039-1698852
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Antibacterial Activity of Calcium Hydroxide Combined with Chlorhexidine Paste and Other Intracanal Medications against Bacterial Pathogens

Abstract: Objectives: The purpose of this study was to assess the in vitro antibacterial activity of four formulations of calcium hydroxide [Ca(OH)2] pastes against Enterococcus faecalis, Staphylococcus aureus, Pseudomonas aeruginosa and Streptococcus mutans. Methods: A broth dilution test was performed, and the lengths of time for different pastes to kill the microbial cells were recorded and statistically analyzed. The following medications were assessed: Group I – Ca(OH)2 + 2.0% chlorhexidine (CHX) gel; Group II – Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Chlorhexine may also present residual antimicrobial activity on the dentine surface after prolonged contact within root canal and also improve antimicrobial efficacy against calcium hydroxide resistant microorganisms. [9] Therefore, used as root canal irrigants and as an intracanal dressing for asepsis of root canal in the present case.…”
Section: Discussionmentioning
confidence: 95%
“…Chlorhexine may also present residual antimicrobial activity on the dentine surface after prolonged contact within root canal and also improve antimicrobial efficacy against calcium hydroxide resistant microorganisms. [9] Therefore, used as root canal irrigants and as an intracanal dressing for asepsis of root canal in the present case.…”
Section: Discussionmentioning
confidence: 95%
“…This drug was introduced in Endodontics in 1920 by Hermann and has been used in different clinical situations since then (2). The effects of CH include antimicrobial activity (2)(3)(4)(5), mechanical blocking to avoid re-infection of the root canal (5,6), capacity to limit root resorption (7,8), induces formation of mineralized tissue (5,6) and promotes repair of periapical and adjacent tissues (2,4).…”
Section: Introductionmentioning
confidence: 99%
“…Tronstad et al (8) suggested that CH in the root canals promotes a pH increase on the external root surface, thus promoting alkalinization of resorption areas on the root surface, by diffusion of hydroxyl ions through the dentinal tubules. Other important characteristic of the dissociation of CH into hydroxyl ions is the ability to inactivate bacterial lipopolysaccharide (LPS), a toxin produced by Gram-negative bacteria commonly found in the root canal system (4,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, E. faecalis has been found to be resistant to this effect due to its capability to go through the dentinal tubules and adapt to altering environments[11]. Various antibacterial agents have been introduced, such as chlorohexidine, metronidazole, bioactive glass, or their combination with Ca(OH) 2 , which were found to be more efficient than Ca(OH) 2 alone in minimizing the number of E. faecalis , with varying degrees of success[12],[13]. Consequently, the discovery and development of the medicaments to control the infection of root canal is urgently needed.…”
Section: Introductionmentioning
confidence: 99%